FINE MOTOR SKILLS THROUGH IMPROVING THE FINGER PAINTING TECHNIQUES DOWN SYNDROME STUDENTS IN SLB JENETALLASA - Hudayah Taiyeb (State University of Makassar, 2016)
The objective of the research is to improve, fine motor ability of Down Syndrome students in class VII SLB Jenetallasa in terms of: painting by using all fingers, painting by using fingers alternately, painting by using eyes-hand coordination. The research is experiment by using descriptive quantitative approach. The research employed Single Subject Research (SSR) with A-B-A design. The stage of basaline A1 of before intervention consisted, intervention stage consisted, and basaline A2 consisted. The main data source/informant of the research was Down Syndrome students class VII with inisials Tl. Data collection technique used was direct observation. The data was processed by counting the percentage of fine motor ability which consisted of 3 aspects, namely: painting by using all fingers, painting by using fingers alternately, dexterity coordination or eyes and hand speed. The data of the research was analyzed by using quantitative descriptive; then, analyzed by using visual graphic presented in a form of Split-Middle-Technique graphic. The result of intervention given indicates that finger painting technique can improve fine motor of Down Syindrome students in class VII at SLB Jenetallasa in terms of: painting by using all fingers, painting by using fingers alternately, eyes-hand coordination. This improvement can be seen through several indicators such as: estimation of direction tendency of each stage which tended to better, the improveme.t of mean level, from basaline 1 (A1) to basaline 2 (A2), the data overlap percentage from to stage tended to be smaller.